Level of nurses’ knowledge concerning the transplant medicine - Makara-Studzińska, Marta; Celiński, Rafał (Polish Journal of Public Health, 2009)
Introduction. Development of transplantology in the world and in Poland is connected with the level of knowledge concerning receiving and transplanting organs. Acquaintance with procedures connected to organs grafting depends on many factors. They include educational level, life environment and occupation. The aim of this study was to examine the knowledge of the nurses concerning the organ and tissues transplantations with relation to the ward they work and their educational level.Material and methods. The examined group consisted of 100 nurses working in the orthopedic, surgical, gynecological and anesthetic wards. The study was performed by the use of questionnaire.Results. The vast majority of nurses, independently from the ward they are working on, answered correctly the questions asked in the survey. All nurses definitely opposing to giving their organs after death correctly answer the question concerning homotransplantations, whereas the lowest percentage of correct answers was stated in nurses decided to give their organs after death. Similar results cannot be found in the accessible literature sources. This result may prove that the lack of acceptance towards organs grafting does not have to result from lack of knowledge but may be a conscious choice.Conclusions. Level of nurses’ knowledge in the field of transplantology is relatively high, independently from the ward they are working on. The knowledge in the field of transplantology infl uences the attitude towards giving one’s organs after death. The level of nurses’ knowledge in the field of transplantology does not depend on their educational level.